Comparison of 3 Days Amoxicillin Versus 5 Days Co-Trimoxazole for Treatment of Fast-breathing Pneumonia by Community Health Workers in Children Aged 2–59 Months in Pakistan: A Cluster-randomized Trial. (28th December 2018) - Sadruddin, Salim; Khan, Ibad ul Haque; Fox, Matthew P; Bari, Abdul; Khan, Attaullah; Thea, Donald M; Khan, Amanullah; Khan, Inamullah; Ahmad, Ijaz; Qazi, Shamim A
Abstract: Background: Globally, most deaths due to childhood pneumonia occur at the community level. Some countries are still using oral co-trimoxazole, despite a World Health Organization recommendation of oral amoxicillin for the treatment of fast-breathing pneumonia in children at the community level. Methods: We conducted an unblinded, cluster-randomized, controlled-equivalency trial in Haripur District, Pakistan. Children 2–59 months of age with fast-breathing pneumonia were treated with oral amoxicillin suspension (50 mg/kg/day) for 3 days in 14 intervention clusters and oral co-trimoxazole suspension (8 mg trimethoprim/kg and 40 mg sulfamethoxazole/kg/day) for 5 days in 14 control clusters by lady health workers (LHW). The primary outcome was treatment failure by day 4 for intervention clusters and by day 6 for control clusters. The analysis was per protocol. Results: Out of the 15 749 cases enrolled in the study, 9153 cases in intervention and 6509 cases in control clusters were included in the analysis. Treatment failure rates were 3.6% (326) in intervention clusters and 9.1% (592) in control clusters. After adjusting for clustering, the risk of treatment failure was lower in intervention clusters (risk diﬀerence [RD] -5.5%, 95% confidence interval [CI] -7.4–-3.7%) than in control clusters. Children with incomplete adherence had a small increase in treatment failure versus those with complete adherence (RD 2.9%, 95% CI 1.6–4.1%). No deaths or serious adverse events occurred. Conclusions: A 3-day course of oral amoxicillin, administered by LHWs, is an effective and safe treatment for fast-breathing pneumonia in children 2–59 months of age. A shorter course of amoxicillin improves adherence to therapy, is low in cost, and puts less pressure on antimicrobial resistance. Clinical Trials Registration: ISRCTN10618300. Abstract : This cluster-randomized trial compared 3-day oral amoxicillin versus 5-day oral co-trimoxazole for the at-home treatment of fast-breathing pneumonia among children aged 2–59 months by community health workers in Pakistan. Oral amoxicillin treatment was significantly better than oral co-trimoxazole treatment.